A contratação de um empresa privada de ensino pela rede pública municipal de Poá-SP (gestão 2005-2008): a voz dos professores do ensino fundamental I - Mirandola, Claudia Barbosa Santana (2010)
This work is the report of a master degree research in the Post- Graduate Program Education: Curriculum, of Public Policies and Curricular and Educational Reform research group, performed in the municipality of Poá - SP. After contracting the company Sol Soft s e Livros Ltda. in 2006, the municipal school system began to receive a didactic and pedagogical package named Sistema Objetivo Municipal de Ensino (SOME). The package contract included the supply of study material to the students as well as orientation manual and qualifying programs to the teachers. The aim of this research is to understand how the contract process of the company was and how teachers gave meaning to their practice after this process. The research started from a documental analysis based on the reading of laws and decrees that regulate the process of municipalization of basic education in the State of São Paulo and the documents related to the public selection process for contracting the company. There were also observation of pedagogical meetings and hearing of twenty one teachers of the first level of basic education through the use of questionnaires. The bibliographical research was based on J. Gimeno Sacristán, Paulo Freire, Michael W. Apple, Henry Giroux and Lisete Arelaro and has contributed to the constitution of hypotheses and instrumental analysis. It was possible to understand how teachers, as direct authors of their pedagogical practice, deal daily with teaching based on study guides. The conclusion is that the low number of students enrolled at private schools compared to those enrolled at the municipal public school network, the absence of infrastructure in the town which would enable full responsibility for basic education and the available financial resources are factors that contribute to turn the public school network into a target market for educational product companies